Hurricane Effects on a Shallow Lake Ecosystem and Its Response to a Controlled Manipulation of Water Level - Karl E. Havens; Kang-Ren Jin; Andrew J. Rodusky; Bruce Sharfstein; Mark A. Brady; Therese L. East; Nenad Iricanin; R. Thomas James; Matthew C. Harwell; Alan D. Steinman (The Scientific World Journal)
In order to reverse the damage to aquatic plant communities caused by multiple years of high water levels in Lake Okeechobee, Florida (U.S.), the Governing Board of the South Florida Water Management District (SFWMD) authorized a "managed recession" to substantially lower the surface elevation of the lake in spring 2000. The operation was intended to achieve lower water levels for at least 8 weeks during the summer growing season, and was predicted to result in a large-scale recovery of submerged vascular plants. We treated this operation as a whole ecosystem experiment, and assessed ecological responses using data from an existing network of water quality and submerged plant monitoring sites. As a result of large-scale discharges of water from the lake, coupled with losses to evaporation and to water supply deliveries to agriculture and other regional users, the lake surface elevation receded by approximately 1 m between April and June. Water depths in shoreline areas that historically supported submerged plant communities declined from near 1.5 m to below 0.5 m. Low water levels persisted for the entire summer. Despite shallow depths, the initial response (in June 2000) of submerged plants was very limited and water remained highly turbid (due at first to abiotic seston and later to phytoplankton blooms). Turbidity decreased in July and the biomass of plants increased. However, submerged plant biomass did not exceed levels observed during summer 1999 (when water depths were greater) until August. Furthermore, a vascular plant-dominated assemblage (Vallisnera, Potamogeton, and Hydrilla) that occurred in 1999 was replaced with a community of nearly 98% Chara spp. (a macro-alga) in 2000. Hence, the lake’s submerged plant community appeared to revert to an earlier successional stage despite what appeared to be better conditions for growth. To explain this unexpected response, we evaluated the impacts that Hurricane Irene may have had on the lake in the previous autumn. In mid-October 1999, this category 1 hurricane passed just to the south of the lake, with wind velocities over the lake surface reaching 90 km h-1 at their peak. Output from a three-dimensional hydrodynamic / sediment transport model indicates that during the storm, current velocities in surface waters of the lake increased from near 5 cm s-1 to as high as 100 cm s-1. These strong velocities were associated with large-scale uplifting and horizontal transport of fine-grained sediments from the lake bottom. Water quality data collected after the storm confirmed that the hurricane resulted in lake-wide nutrient and suspended solids concentrations far in excess of those previously documented for a 10-year data set. These conditions persisted through the winter months and may have negatively impacted plants that remained in the lake at the end of the 1999 growing season. The results demonstrate that in shallow lakes, unpredictable external forces, such as hurricanes, can play a major role in ecosystem dynamics. In regions where these events are common (e.g., the tropics and subtropics), consideration should be given to how they might affect long-term lake management programs.